Field measurement of temperature and leaf growth on maize/bean inter-crop - Tesfuhuney, Weldemichael Abraha (University of the Free State, 2001)
Notwithstanding the emphasis of research on the intensification of sole-crop systems, the practice of inter-cropping remains widespread. Evidence is accumulating that indicates that under many situations it may represent a more efficient use of natural resources. Much of the basic information on the response of leaf growth to a single environmental factor was obtained during the 1960s when controlled environment facilities became available, yet it proved difficult to extrapolate results obtained in a controlled environment to the field situation. From this background emerged the notion that temperature constitutes one of the main environmental factors influencing leaf growth at the field level for both monocotyledonous and dicotyledonous crops. Sole- and inter-crop maize (Zea mays L.) and dry beans (Phaseolus vulgaris L.) were grown in order to examine the mechanisms by which temperature influences leaf growth during the early growth stage using of three consecutive planting dates in summer. For daily measurements of leaf growth 15 individual plant samples were measured from each replicated plot. Temperature variations were observed during the three planting dates, namely in November, January and March, from the automatic weather station at the experimental site. Generally the temperature increased gradually from the first planting in November until late January during the second planting and thereafter decreased from the beginning of February to reach the lowest temperature in May. Due to the difference in temperature at the consecutive planting dates the seedling emergence in the third planting showed took longer. From daily leaf length measurements of sole and inter-crop maize the leaf length proved to be almost linear with time (days after planting). During the first planting, the leaf growth was more rapid and the largest leaf size was recorded. In the case of the third planting it took a longer time to reach the same length due to low temperatures, while in the second planting heat stress caused the maize crop to grow at a slower rate and reach a smaller size compared to the other planting dates. For sole and inter-crop beans during the first planting, the leaf growth displayed some form of sigmoid curve, whereas In the second planting due to the high temperatures the growth appeared to have two sigmoidal cycles during the growing period. For simplicity in the analysis, the mean leaf growth rate, and the slope (rate) of a linear regression was applied for each leaf length. In maize, both approaches showed an increase in its rate with increasing leaf number with the exception of leaf 11 in first planting, whereas in the third planting the leaf growth was lower and fewer leaves resulted. In beans, these two approaches showed some differences during the growth period for all planting dates but they followed the same general trend of growth rate. Comparing the two approaches, the slope of the linear regression could render a more representative rate provided the leaf growth was linear with time . On the other hand, the behaviour of leaf growth as a function of temperature was recorded by searching for the most appropriate thermal responses by curve fitting, using the Richards function model. This gave the highest correlation of maize leaf growth with thermal time. Generally, in all planting dates and cropping systems there was a significant correlation between the leaf growth variables and thermal time after emergence when using 10°C and 30°C as Tbase and extreme temperatures respectively. In contrast, for the bean crop the estimates displayed a weak correlation and it became important to consider other environmental factors along with the temperature variations. The study also assessed the field measurements of hourly leaf extension rate versus leaf temperature for sole- and inter-cropped maize plants. On each cropping system 6 auxanometers were installed to measure hourly leaf extension rate along with leaf temperatures for three days during warm and cool periods. It was shown that the leaf extension rate (LER) is one of the first components of plant growth to be affected by short period changes in temperature. Its importance led to the measurement of hourly growth rate in conjunction with leaf temperature. In this study the LER of maize as an average for three hours was used during both warm and cool periods. The measured rate was higher during the warm period, yet declined sharply above 29.5°C. Nonetheless, most of the data concentrated on temperatures up to 24°C with very few measurements In the range of 29- 29.5°C of temperatures. These values were used as common values for both fitting lines. The combination of data from both periods produced two linear regression equation. LER reached a maximum (3.2 mm h-1) at 27.8°C and was expected to be zero at the lower temperature of 6.2°C and the higher temperature of 35.3°C. These measurements of leaf growth and temperature show how temperature variations during the early growth stage of sole- and inter-crop maize/bean influence the leaves' subsequent expansion to final size. It was also observed that temperature greatly influences the rate of leaf expansion in chronological time, particularly for leaves in the field. It is difficult to resolve leaf growth data without recourse to thermal time analysis. From the study it was seemed, that accurate estimation of Tbase and Tmax as well as the method of calculating the thermal time play a great role in assessment of possible variation of leaf growth in different planting dates.

Ongeag die klem wat navorsing op die verskerping van enkelbou-stelsels plaas, bly die beoefening van interbou-stelsels baie algemeen. Toenemende getuienis dui daarop dat dit sigself in vele toepasslnqs tot 'n doeltreffender benutting van natuurlike hulpbronne mag leen. Baie van die basiese inligting oor die reaksie van blaargroei op 'n enkele omgewingsfaktor is gedurende die 1960's ingewin toe beheerde omgewingsgeriewe beskikbaar geword het: tog het dit moelik geblyk te wees om uitslae wat in 'n beheerde omgewing verkry is, tot die veldsituasie uit te brei. Vanuit hierdie agtergrond het die denke ontstaan dat temperatuur een van die hoof omgewingsfaktore is wat blaargroei in die veld, beide op monocotyledoneuse en dicotyledoneuse gewasse, beinvloed. Enkel- en tussenverboude mielies (Zea mays L.) sowel as bone (Phaseolus vulgris L.) is gekweek met die doelom die meganismes waardeur temperatuur blaargroei beinvloed te ondersoek tydens hul vroeë groeistadium gedurende drie opeenvolgende planttye in die somer. Vyftien individuel plante is daagliks op drie ewebeeldige persele vir blaargroei gemeet. Temperatuurwisselings is tydens die drie plantdatums deur die nabygeleë outomatiese weerstasie aangeteken en wel in November, Januarie en Maart. Oor die algemeen het die temperatuur geleidelik toegeneem vanaf die eerste planting in November tot laat Januarie van die tweede planting en daarna gedaal van die begin van Februarie tot sy laagste vlak in Mei. Vanweë die temperatuurverskille vir die opeenvolgende plantdatums het die saadopkoms oor die derde planting langer gevat. Daaglikse bepalings van blaarlengte van enkel- en tussenverboude mielies het feitlik 'n reglynige verband met tyd (dae na planting) getoon. Gedurende die eerste planting was die blaargroei vinnig en is die grootste blaargrootte aangeteken. In die geval van die derde planting het bereiking van dieselfde grootte langer geneem weens lae temperature, terwyl hittespanning in die tweede planting stadiger groei en 'n kleiner finale grootte as In die ander gevalle veroorsaak het. Vir enkel- en tussenverboude bone met die eerste planting het blaargroei 'n tipe sigmoidale kuiwe vertoon, terwyl dit vanweë die hoë temperature in die tweede planting twee sigmoidale siklusse tydens die groeiperiode gevolg het . Vie Eenvoudigheidshalwe van in die ontleding is gemiddelde blaargroei en die helling van 'n lineêre regressiekurwe gebruik gemaak. Vir mielies het beide benaderings 'n toename in die groeitempo met toename in blaartelling getoon, met die uitsondering van blaar 11 van die eerste planting, terwyl beide die blaartal en groei met die derde planting afgeneem het. Vir bone het die twee benaderings sommige verskille tydens groei getoon oor en die plantdatums, hoewel hulle dieselfde algemene verloop van groeikoers gehad het. 'n Vergelyking tussen die twee benaderings dui aan dat die helling van lineêre regressie moontlik 'n meer verteenwoordigende koers kan lewer mits die blaargroei lineêr met tyd is Daarteenoor is die gedrag van blaargroei as 'n funksie van temperatuur aangeteken deur met behulp van kurwepassing die toepaslikste termiese reaksies deur middel van die Richards funksiemodel na te spoor. Dit het die beste korrelasie van mielieblaargroei met termiese tydindek gelewer. Dit dui op 'n beter sigmoidale kurwe vir mielieblaargroei deur die tydsduur van elke temperatuurvlak te gebruik. Oor die algemeen was daar vir al die plantdatums en verbousisteme aansienlike korrelasie tussen die blaargroeiveranderlikes en termiese tyd na opkoms mits 10°C en 30°C as Tbase gebruik word. In teenstelling hiermee het die beramings vir die bone 'n swak korrelasie gelewer en het dit belangrik begin lyk om ander omgewingsfaktore saam met die temperatuurvariasies te oorweeg. Die studie het ook die veldmetings van uurlikse blaarverlengingskoers teen blaartemperatuur vasgestel vir enkel- en tussenverboude mielieplante. Op elke verboustelsel is 6 auxanometers ingebou om uurlikse blaarverlengingskoers saam met blaartemperatuur oor drie dae tydens warm en koel tydperke te meet. Dit is aangetoon dat die blaarverlengingskoers (LER) een van die eerste komponente van plantgroei is wat deur kortduur temperatuurveranderinge geraak word. Die belangrikheid hiervan het gelei tot die meting van uurlikse groeitempo in samehang met temperatuur. In hierdie studie is die LER van mielies as 'n gemiddelde oor drie uur tydens beide warm en koel periodes gebruik. Die gemete koers was hoër gedurende die warm tydperk, maar het tog skerp gedaal bo 29.5°C. Meeste van die data was egter toegespits op temperature net tot 24°C, met min temperature in die 29-29.5°C interval. Hierdie waardes is as gemeenskaplike waardes vir beide paslyne gebruik. Die kombinering van data vir beide periodes het twee lineêre regressievergelyking gegee. LER het 'n maksimum (3.2mm h") teen 27.8°C bereik en het op 'n verwagte nullesing by die laer temperatuur van 6.2°C en die hoer temperatuur van 35.3°C gedui. Hierdie metings van blaargroei en temperatuur toon aan hoe temperatuurwisselings tydens die vroeë groeistadium van enkel- en tussenverboude mielises/boontjies die blare se uitsetting tot finale grootte beinvloed. Daar is ook waargeneem dat temperatuur die tempo van blaarvergroting in chronologiese tyd aansienlik beinvloed, veral in blare op die akker. Dit is moeilik om blaargroeidata te verwerk sonder toevlug na termiese data-ontleding. Uit die studie is die gevolgtrekking gemaak dat akkurate beraming van Tbase en Tmax en, sowel as die metode van berekening van termiese tyd 'n groot rol speel in die bepaling van moontlike variasie in blaargroei vir veskillende plantdatums.
Dissertation (M.Sc.Agric. (Agrometeorology))--University of the Free State, 2001
Keywords: Planting date; Thermal time; Richards function; Leaf length; Leaf number; Optimum temperature; Leaf growth curves; Leaf extension rate (LER); Auxanometer; Leaf temperature; Intercropping; Leaves -- Growth; Corn -- Effect of temperature on; Legumes -- Effect of temperature on